A conceptual framework of an effectiveness of talent management in improving organisational performance at BSN: leadership style as a moderator - Nasir, Yong Salmah; Mohtar, Shahimi; Ariffin, Ahmad Shabudin (Akademia Baru, 2017)
This paper conceptualises to investigate the effectiveness of talent management (PB) in improving the organisation performance as leadership style (GK) acted as the moderator. It highlighted on related independent variables namely: employee attraction, retention, development, motivation, and succession planning. Dependent variable namely: the growth rate of sales, operating result and product of human resources. Hence, an ability to conceptualise, observe and give due recognition to the possible relation amongst these variables in question by the prospective employees of one of the Malaysian Government-Owned Banks. The conceptual of talent management as the dimension is the attraction, retention, motivation, development, and succession planning. The study is strengthened further by the problem statement, research questions, as well as the objectives of the study conducted by the research gaps identified.